Effects of cancer treatment on household impoverishment: a multicentre cross-sectional study in China. Issue 6 (30th June 2021) - Fu, Wenqi; Shi, Jufang; Zhang, Xin; Liu, Chengcheng; Sun, Chengyao; Du, Yupeng; Wang, Hong; Liu, Chaojie; Lan, Li; Zhao, Min; Yang, Li; Bao, Burenbatu; et al.
Abstract : Objectives: To determine the incidence and intensity of household impoverishment induced by cancer treatment in China. Design: Average income and daily consumption per capita of the households and out-of-pocket payments for cancer care were estimated. Household impoverishment was determined by comparing per capita daily consumption against the Chinese poverty line (CPL, US$1.2) and the World Bank poverty line (WBPL, US$1.9) for 2015. Both pre-treatment and post-treatment consumptions were calculated assuming that the households would divert daily consumption money to pay for cancer treatment. Participants: Cancer patients diagnosed initially from 1 January 2015 to 31 December 2016 who had received cancer treatment subsequently. Those with multiple cancer diagnoses were excluded. Data sources: A household questionnaire survey was conducted on 2534 cancer patients selected from nine hospitals in seven provinces through two-stage cluster/convenience sampling. Findings: 5.89% (CPL) to 12.94% (WBPL) households were impoverished after paying for cancer treatment. The adjusted OR (AOR) of post-treatment impoverishment was higher for older patients (AOR=2.666–4.187 for ≥50 years vs <50 years, p<0.001), those resided in central region (AOR=2.619 vs eastern, p<0.01) and those with lower income (AOR=0.024–0.187 in higher income households vs the lowest 20%, p<0.001). The patients without coverage from social health insurance had higher OR (AOR=1.880, p=0.040) of experiencing post-treatment household impoverishment than those enrolled with the insurance for urban employees. Cancer treatment is associated with an increase of 5.79% (CPL) and 12.45% (WBPL) in incidence of household impoverishment. The median annual consumption gap per capita underneath the poverty line accumulated by the impoverished households reached US$128 (CPL) or US$212 (WBPL). US$31 170 395 (CPL) or US$115 238 459 (WBPL) were needed to avoid household impoverishment induced by cancer treatment in China. Conclusions: The financial burden of cancer treatment imposes a significant risk of household impoverishment despite wide coverage of social health insurance in China.